Opportunities and limits of the one gene approach: the ability of Atoh1 to differentiate and maintain hair cells depends on the molecular context - Jahan, Israt; Pan, Ning; Fritzsch, Bernd (Frontiers in Cellular Neuroscience, 2015)
Atoh1 (Math1) was the first gene discovered in ear development that showed no hair cell (HC) differentiation when absent and could induce HC differentiation when misexpressed. These data implied that Atoh1 was both necessary and sufficient for hair cell development. However, other gene mutations also result in loss of initially forming HCs, notably null mutants for Pou4f3, Barhl1, and Gfi1. HC development and maintenance also depend on the expression of other genes (Sox2, Eya1, Gata3, Pax2) and several genes have been identified that can induce HCs when misexpressed (Jag1) or knocked out (Lmo4). In the ear Atoh1 is not only expressed in HCs but also in some supporting cells and neurons that do not differentiate into HCs. Simple removal of one gene, Neurod1, can de-repress Atoh1 and turns those neurons into HCs suggesting that Neurod1 blocks Atoh1 function in neurons. Atoh1 expression in inner pillar cells may also be blocked by too many Hes/Hey factors but conversion into HCs has only partially been achieved through Hes/Hey removal. Detailed analysis of cell cycle exit confirmed an apex to base cell cycle exit progression of HCs of the organ of Corti. In contrast, Atoh1 expression progresses from the base toward the apex with a variable delay relative to the cell cycle exit. Most HCs exit the cell cycle and are thus defined as precursors before Atoh1 is expressed. Atoh1 is a potent differentiation factor but can differentiate and maintain HCs only in the ear and when other factors are co-expressed. Upstream factors are essential to regulate Atoh1 level of expression duration while downstream, co-activated by other factors, will define the context of Atoh1 action. We suggest that these insights need to be taken into consideration and approaches beyond the simple Atoh1 expression need to be designed able to generate the radial and longitudinal variations in hair cell types for normal function of the organ of Corti.